MENGHAPUS KEKERASAN DALAM RUMAH TANGGA DENGAN KAJIAN NORMATIF-YURIDIS: ANALISIS INTERDISIPLINER DENGAN PEMBEDAAN NASH OBJEKTIF DAN TEMPORAL - Nasution, Khoiruddin (JURIS (Jurnal Ilmiah Syariah), 2018)
This paper is intended to describe the efforts that can be done to eradicate the violence in domestic life, especially to the wife. There are three theories of the interdisciplinary study; 1) the theory of classification of nash, 2) the theory of the effectiveness of the law, and 3) the theory of social action. Based on the data anlysis it could be found that first, there are a number of factors being the cause and source of violence against wives in domestic life. Second, understanding nash would distinguish objectives nash (maqâsid) from the temporal nash (wasâ’il). Third, it is important to build a legal culture of community, especially between husband and wife in domestic life, and importantly also changed a traditional behavior of society into a rational behavior. Fourth, the course of marriage becomes one of effective media introduced the law in in society, especially for husband and wife, in order to build a legal culture and change the traditional behavior of the society to be a rational one.